THEOLOGY OF PEACE BASED ON RELIGIOUS HARMONY IN ASGHAR ALI ENGINEER’S PERSPECTIVE - Hidayatulloh, Taufik; Saumantri, Theguh (ILMU USHULUDDIN, 2023)
This article will explore Asghar Ali Engineer’s ideas on the significance of religious harmony and examine how this concept is manifested through his formulated theology of peace. The research method used in this study is literature review with a philosophical approach using hermeneutic and text analysis techniques through verstehen. The results of this study explain that the theology of peace sees religion as a source of values and spirit that encourage humans to live together in peace and harmony. Asghar Ali Engineer suggests that Muslims prioritize the principles of peace, such as the understanding of Islam, the meaning of jihād, movement, and the application of justice. In addition, according to Asghar Ali’s perspective, Muslims must cultivate values that can realize religious harmony and peace, such as anti-violence, justice, truth, tolerance, love, and compassion.